Longitudinal CITE-Seq profiling of chronic lymphocytic leukemia during ibrutinib treatment: evolution of leukemic and immune cells at relapse - Sarah Cadot; Carine Valle; Marie Tosolini; Frederic Pont; Laetitia Largeaud; Camille Laurent; Jean Jacques Fournie; Loic Ysebaert; Anne Quillet-Mary (BMC, 2020)
Abstract Background Ibrutinib, an irreversible Bruton Tyrosine Kinase (BTK) inhibitor, has revolutionized Chronic Lymphocytic Leukemia (CLL) treatment, but resistances to ibrutinib have emerged, whether related or not to BTK mutations. Patterns of CLL evolution under ibrutinib therapy are well characterized for the leukemic cells but not for their microenvironment. Methods Here, we addressed this question at the single cell level of both transcriptome and immune-phenotype. The PBMCs from a CLL patient were monitored during ibrutinib treatment using Cellular Indexing of Transcriptomes and Epitopes by sequencing (CITE-Seq) technology. Results This unveiled that the short clinical relapse of this patient driven by BTK mutation is associated with intraclonal heterogeneity in B leukemic cells and up-regulation of common signaling pathways induced by ibrutinib in both B leukemic cells and immune cells. This approach also pinpointed a subset of leukemic cells present before treatment and highly enriched during progression under ibrutinib. These latter exhibit an original gene signature including up-regulated BCR, MYC-activated, and other targetable pathways. Meanwhile, although ibrutinib differentially affected the exhaustion of T lymphocytes, this treatment enhanced the T cell cytotoxicity even during disease progression. Conclusions These results could open new alternative of therapeutic strategies for ibrutinib-refractory CLL patients, based on immunotherapy or targeting B leukemic cells themselves.